Strategies for disaster management and the role of effective governance in Nepal - Jaya Narayan Acharya; Werapong Koedsin; Kuaanan Techato (Journal of Water and Land Development)
This paper examines the crucial interplay between governance and disaster management in Nepal, a nation frequently assailed by natural disasters such as earthquakes, landslides, and floods. Despite substantial progress in disaster risk reduction (DRR) frameworks, particularly following the devastating 2015 earthquake, challenges persist, primarily due to governance issues. Through a mixed-methods approach involving structured questionnaires and indepth interviews with government officials, local leaders, and non-governmental organisation (NGO) representatives, this study explores the effectiveness of disaster management strategies underpinned by governance practices. The research uncovers significant operational, institutional, and environmental challenges that hinder effective disaster management. Key findings indicate bureaucratic delays, poor coordination, and inadequate resource allocation as major impediments, while community engagement and the integration of local knowledge emerge as critical success factors. Furthermore, the study highlights the adverse effects of governance traps, such as political interference and lack of transparency, which exacerbate the vulnerability of disaster-stricken communities. The paper argues for the necessity of robust governance structures that are transparent, accountable, and inclusive, to enhance disaster resilience and response in Nepal. Recommendations are made for strengthening local capacities, improving inter-agency coordination, and leveraging technology to predict and manage disasters more effectively. By addressing these governance-related issues, Nepal can enhance its disaster preparedness and ensure a more resilient future for its population.